Prevalence and One-Year Survival of Selected Major Congenital Anomalies in Germany: A Population-Based Cohort Study - Turial, Salmai; Stimming, Friederike; Lux, Anke; Koehn, Andrea; Rissmann, Anke (European Journal of Pediatric Surgery, 2022)
Introduction Congenital anomalies play an important role in infant mortality worldwide. The present study aims to present the current data on the prevalence rates and the 1-year survival rates for selected major congenital anomalies in Saxony-Anhalt, Germany.Materials and Methods The data were collected systematically by the Malformation Monitoring Centre Saxony-Anhalt. Cohort from 2000 to 2017 was retrospectively analyzed to determine the prevalence rates and the survival rates of nine major congenital anomalies. The survival analysis was conducted, including all pregnancy outcomes and various risk factors.Results In total, 1,012 cases of the selected congenital anomalies were registered. The total prevalence rates ranged from 2.5 (congenital diaphragmatic hernia [CDH]) to 5.8 (spina bifida [SB]) per 10,000. The live birth prevalence was lower. In total, 88.3% of live-born cases survived the first year. The 1-year survival rate of all cases, including fetal losses, was merely 61.7%. There was no continual improvement in survival during the study period noted. The 1-year survival rate was 35.7% for “genetic” malformations, 57.6% for “multiple congenital anomalies,” and 68.6% for “isolated” cases, with 44.6% for prenatally detected anomalies and 85.2% for postnatally identified anomalies. Gestational age less than 31 weeks and birth weight below 1,000 g affected the survival rate adversely.Conclusion The survival rate of infants suffering from congenital anomalies in Saxony-Anhalt is comparable to that reported by national and international studies. Registering all pregnancy outcomes irrespective of whether they result in a live birth, stillbirth, or fetal loss in a malformation register seems to be important as it affects the statistical survival analysis in general.
Keywords: congenital anomaly; infant; survival; prevalence; pregnancy outcome